2020
DOI: 10.3389/fpsyg.2020.02205
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Skill Growth and Evaluating Change: Unconditional and Conditional Approaches to Latent Growth Cognitive Diagnostic Models

Abstract: During the past decade, cognitive diagnostic models (CDMs) have become prevalent in providing diagnostic information for learning. Cognitive diagnostic models have generally focused on single cross-sectional time points. However, longitudinal assessments have been commonly used in education to assess students' learning progress as well as evaluating intervention effects. Thus, it becomes natural to identify longitudinal growth in skills profiles mastery, which can yield meaningful inferences on learning. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
(61 reference statements)
0
7
0
Order By: Relevance
“… 15 , 16 , 17 , 18 Learning trajectories represent longitudinal patterns of developmental progress, measuring growth and acquisition of competencies over time. 15 , 16 In this regard, identifying meaningful patterns that reveal inflection points in learner’s developmental progress and examining factors influencing the variability of milestones level (eg, program-level effects) can be informative. Although different patterns of developmental progress may exist, a learner may improve consistently during the initial phase of training but plateau at later stages; learners may also progress with varying inflection points (shift in the direction of the slope) during training when their performance stagnates or decreases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 , 16 , 17 , 18 Learning trajectories represent longitudinal patterns of developmental progress, measuring growth and acquisition of competencies over time. 15 , 16 In this regard, identifying meaningful patterns that reveal inflection points in learner’s developmental progress and examining factors influencing the variability of milestones level (eg, program-level effects) can be informative. Although different patterns of developmental progress may exist, a learner may improve consistently during the initial phase of training but plateau at later stages; learners may also progress with varying inflection points (shift in the direction of the slope) during training when their performance stagnates or decreases.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Longitudinal assessments can be described as learning trajectories to measure the developmental progression of learners. [15][16][17][18] Learning trajectories represent longitudinal patterns of developmental progress, measuring growth and acquisition of competencies over time. 15,16 In this regard, identifying meaningful patterns that reveal inflection points in learner's developmental progress and examining factors influencing the variability of milestones level (eg, program-level effects) can be informative.…”
Section: Introductionmentioning
confidence: 99%
“…To provide theoretical support for the concept of a longitudinal learning diagnosis, several longitudinal learning diagnosis models (LDMs) have been proposed in recent years (for a review, see Pan, Qin, & Kingston, 2020; Zhan, 2020b). Existing longitudinal LDMs can be divided into two main types: latent transition analysis‐based models (e.g., Kaya & Leite, 2017; Li, Cohen, Bottge, & Templin, 2016; Madison & Bradshaw, 2018; Wang, Yang, Culpepper, & Douglas, 2018; Wen, Liu, & Zhao, 2020; Zhang & Wang, 2019) and higher‐order latent structure‐based models (e.g., Lee, 2017; Lin, Xing, & Park, 2020; Huang, 2017; Pan et al., 2020; Zhan, 2020c; Zhan, Jiao, Liao et al., 2019). The former estimates the transition probabilities from one latent attribute (profile) to another or the same latent attribute (profile).…”
Section: Introductionmentioning
confidence: 99%
“…Zhan, Jiao, Liao, et al (2019) employed a similar strategy in the development of a higher-order longitudinal variant of the DINA model (Junker & Sijtsma, 2001;Macready & Dayton, 1977;Maris, 1999), and Zhan, Jiao, Man, et al (2019) demonstrated how to estimate the longitudinal DINA model under a Bayesian setting. Lin et al (2020) introduced a growth curve approach for modeling higher order traits where covariates are introduced into the continuous component. Most recently, Zhan, Ma, et al (2020) developed a higher-order latent trait DCM for hierarchical attribute structures, Zhan (2020a) introduced a Markov estimation strategy for immediate diagnostic feedback, and Zhan (2021) proposed a longitudinal probabilistic DCM which treats attributes as probabilistic entities.…”
Section: Introductionmentioning
confidence: 99%